Front Cover: Highly Porous Hybrid Metal–Organic Nanoparticles Loaded with Gemcitabine Monophosphate: a Multimodal Approach to Improve Chemo‐ and Radiotherapy (ChemMedChem 3/2020). (5th February 2020) - Li, Xue; Porcel, Erika; Menendez‐Miranda, Mario; Qiu, Jingwen; Yang, Xiaomin; Serre, Christian; Pastor, Alexandra; Desmaële, Didier; Lacombe, Sandrine; Gref, Ruxandra
Abstract : The Front Cover shows the first application of radioenhancers made of nanoscale metal–organic frameworks (nanoMOFs), loaded with Gemcitabine‐monophosphate, a radiosensitizing anticancer drug. Iron trimesate nanoMOFs possess a regular porous structure with oxocentered Fe trimers separated by around 5 Å. This porosity is favorable to diffuse the electrons emitted from nanoMOFs activated by γ radiation, leading to generation of hydroxyl radicals which create nanoscale damages in cancer cells. Both nanoMOFs and incorporated drug contribute to improve radiation efficacy. The radiation enhancement factor of Gem‐MP loaded nanoMOFs reaches 1.8, one of the highest values reported. More information can be found in the Full Paper by Ruxandra Gref, Sandrine Lacombe et al. on page 274 in Issue 3, 2020 (DOI: 10.1002/cmdc.201900596 ).